MONOCLONAL ANTIBODIES AGAINST OUTER MEMBRANE PROTEIN PASTEURELLA MULTOCIDA STRAIN DOMPU - Sri Murwani; Widya Asmara (Jurnal Sain Veteriner, 1998)
Monoclonal antibodies were produced against outer membrane protein of Pasteurella multocida strain Dompu. The bacterial isolate was obtained from [he bacteria! collection held at Microbiology Laboratory, Faculty of Veterinary Medicine, Gadjah Mada University. Irs purity and patogenicily has beeen tested.Killed PatTeurella multocida were used ro immunized 7 female, 8-10 week old of Balb/ c mice. Cell fusion between limphocytes and myeloma cells (2:1) were carried out by PEG stimulation and bybrids were cultured in  HAT medium.The OMP were prepared from sonicated organism using centrifugallon in the presense of sarcosyL These antigens were than used to select antibody producing hvbridomas ELISA and cloning of hybridomas were done by serial dilution method.Four hybridomas clones were obtained, till producing monoclonal antibodies which reacted specifically against OMP Pasietirelta multacida stain Dompu.